New times, new strategies: a reflection from care - Juana Rocío Reyes Bautista; Fernando Jesús Robledo Cárdenas; Mario Merino Casto (Universidad de Alicante, 2012)
The evolution of the Andalucian society in which we are immerse is progressively changing such typically traditional society. This overall evolution has an impact on the culture of home care, and assisting the dependent elderly is one of the most affected aspects. An imaginary situation is debated here about a nurse judgement in which the patient is the real Andalucian society itself. The situation and possibilities are discussed from the perspective of care and based on standarised taxonomies, all from a hypothetic point of view but based on a growingly frequent reality in Andalucian hospitals.